Fabrication and compressive properties of low to medium porosity closed-cell porous aluminum using PMMA space holder technique - Jamal, Nur Ayuni; Ai Wen, Tan; Yusof, Farazila; Katsuyoshi, Kondoh; Hisashi, Imai; Anuar, Hazleen (MDPI AG, 2016)
In recent years, closed-cell porous Aluminum (Al) has drawn increasing attention, particularly in the applications requiring reduced weight and energy absorption capability such as in the automotive and aerospace industries. In the present work, porous Al with closed-cell structure was successfully fabricated by powder metallurgy technique using PMMA as a space holder. The effects of the amount of PMMA powder on the porosity, density, microstructure and compressive behaviors of the porous specimens were systematically evaluated. The results showed that closed-cell porous Al having different porosities (12%–32%) and densities (1.6478 g/cm3, 1.5125 g/cm3 and 1.305 g/cm3) could be produced by varying the amount of PMMA (20–30 wt %). Meanwhile, the compressive behavior results demonstrated that the plateau stress decreased and the energy absorption capacity increased with increasing amount of PMMA. However, the maximum energy absorption capacity was achieved in the closed-cell porous Al with the addition of 25 wt % PMMA. Therefore, fabrication of closed-cell porous Al using 25 wt % PMMA is considered as the optimal condition in the present study since the resultant closed-cell porous Al possessed good combinations of porosity, density and plateau stress, as well as energy absorption capacity.